Probiotics - should pediatricians and neonatologists use them? A literature review - Marcicka, Justyna; Mądry, Wojciech; Mazurkiewicz, Aleksandra; Kołodziej, Magdalena; Męczyńska, Joanna; Saiuk, Nazarii; Kozicz, Michał Andrzej; Seredyński, Tomasz; Wojciechowska, Adriana; Salasa, Weronika (Quality in Sport, 2024)
In recent years, interest in probiotics in publications has been steadily increasing. This is associated with the discovery of the relationship between disruptions in the gut microbiome and dysfunction of the immune system, and consequently, the development of various diseases and allergies. The composition of the natural gut microbiota in newborns can undergo changes, and as a result, we can influence it both prenatally and postnatally. According to available research, factors influencing it include the timing and method of delivery, maternal antibiotic use during pregnancy and breastfeeding, as well as antibiotic use in newborns after birth, and the method of feeding the child. It is suspected that disturbances in the composition of gut microbiota from the earliest stages of life contribute to the development of disorders such as functional gastrointestinal disorders (diarrhea, constipation, irritable bowel syndrome), inflammatory bowel diseases, allergies, atopic dermatitis, neurodevelopmental disorders (autism spectrum disorders), and increased risk of obesity in later years of the child’s life. When significant dysbiosis occurs, stimulating the growth of protective and nutritive autochthonous bacteria on the intestinal epithelium is difficult to achieve in any other way than using appropriately selected probiotic strains. However, it is important to remember to choose probiotics with a well-researched quantitative and qualitative composition, and to select them depending on the underlying disease, as well as the age and other conditions of the patient.